Links between the price of butter in Poland and in selected foreign markets - Domagała, Joanna (Powiązanie cen masła w Polsce z wybranymi rynkami świata, 2021)
The aim of the paper was to determine the links between price of butter in Poland and in other selected countries. The article used secondary data for the monthly price of butter at country level collected by the Milk Market Observatory and the Italian Dairy Economic Consulting Portal for 2000-2017. The analyses covered two periods: 2000-2007 and 2008-2017. The article used the Johansen cointegration tests, and Granger’s causality analysis. The analyses in the first stage concerned the links between butter prices in Poland and those in Western Europe, the USA and Oceania. In the second stage, the links between butter prices in Poland and selected EU countries were identified. The results confirmed the stronger link between the price of butter in Poland and in Western Europe and Oceania. It is worth noting that this occurred mainly in the period after the financial crisis. Within the EU, butter prices in Belgium, the Czech Republic, Germany, Ireland and the Netherlands were strongly related to the price in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 3, s. 13-25
Keywords: butter market; price; time series analysis; rynek masła; ceny; analiza szeregów czasowych